Remarks about Reliable Identification of Probability Distributions of Two Independent Objects - Haroutunian, Evgueni A.; Hakobyan, Parandzem M. (Mathematical Problems of Computer Science, 2021)
In this paper we present some additions to results on logarithmically asymptotically optimal identification of probability distributions of two independent objects, published by authors in 2007.